Clarice Lispector: Da solidão de não pertencer à quarta dimensão - Torre, Daniela Della (2006)
The work Clarice Lispector: about the loneliness of not belonging to the fourth dimension discusses the major constitutive issues of people s way of being. The dialogue with Clarice Lispector, a well known person, with a special way of being, brings light to this discussion and gives its contribution while presenting its singularity. This study is based on Donald W. Winnicott s psychoanalytical assumptions and especially on Gilberto Safra s id eas about the personal idiom . The story of Clarice, the studies about her, the testimonials she left during her life and the new reading of her works allow us to unveil her personal idiom the mission/issue of belonging/not belonging, her loneliness and silence that appears in her writings. An Artisan s essay tries do reconstruct this career, this way of being. From The loneliness of not belonging to the fourth dimension the personal idiom designs itself in an ontological perspective. In the beginning there is a mission that does not allow a future. But, during her life, it was positioned as an issue and the not belonging and the wish of belonging appear as fundamental aspects. Clarice s loneliness is the center of a secret, of a mystery, behind her thoughts. While the silence, source of my words, becomes her expected presence. The word, fourth dimension, when it appears, touches her hidden face and saves her. Clarice s clarity in face of existence and human condition allow us to discover her humanity, beyond herself. With the word she discovers the destiny of her issues, she builds the bridge between to be and not to be in witch we find singularities of the human being